Analyzing rare diseases terms in biomedical terminologies - Erika Pasceri (JLIS.it, 2012)
Rare disease patients too often face common problems, including the lack of access to correct diagnosis, lack of quality information on the disease, lack of scientific knowledge of the disease, inequities and difficulties in access to treatment and care. These things could be changed by implementing a comprehensive approach to rare diseases, increasing international cooperation in scientific research, by gaining and sharing scientific knowledge about and by developing tools for extracting and sharing knowledge. A significant aspect to analyze is the organization of knowledge in the biomedical field for the proper management and recovery of health information.